Exploring Changes In The European Democracy Promotion Policy In Egypt After The 2011 Events ‘Same Cocktail, Different Portions’ - Shehata, Abdallah (AUC Knowledge Fountain, 2014)
The EU has been engaged in promoting democracy in Egypt for the last two decades. In 2011, Egyptians took part in huge demonstrations resulting in changes in the Egyptian political reality. This study investigates the changes in the European Union democracy promotion policy in Egypt after the events of 2011, causes of policy change and policy change mechanisms. This study takes a comparative case study approach, juxtaposing European Union democracy promotion policies in Egypt at different points of transition. The study concludes that there were no major changes in the EU policies but there were only some corrections in the current strategy. The study indicates that the change in the local situation in Egypt was the main reason behind EU democracy promotion policy change.